The History of the Development of Domestic Chemical Intelligence Tools - A. N. Petukhov; V. V. Vilchik; T. V. Shustikova; D. M. Imamov; M. S. Molchanov (Вестник войск РХБ защиты, 2024)
This article is dedicated to the history of the development of chemical reconnaissance and control means of the Workers' and Peasants' Red Army, the Soviet and Russian armies. This plot has never been covered previously in open literature. The aim of the work is to give a sketch of the development of chemical reconnaissance and control means from the First World War to the present day. The source base - documentary sources containing information about the chronology of acceptance for supply of chemical reconnaissance technical means, technical descriptions, manuals and operating instructions, as well as literature containing information about the design and principles of operation of these means. The method of analysis is descriptive. The discussion of the results. The most important factor that has influenced the development of means of indication was the development of chemical weapons. Аn analysis of information sources showed that before the Second World War, exclusively the chemical indication method was used. Since the late 1950s, due to the appearance of the organophosphorus agents, along with the chemical methods of indication, the biochemical methods began to be actively used both in military and in special means of chemical reconnaissance. The ionization method was first implemented in the early 1970s, the remote method (laser sensing) – in the late 1980s. Ion mobility spectrometry has been used since the late 1990s, gas chromatography-mass spectrometry and FT-IR spectroscopy – since the early 2000s. The technology of semiconductor sensors has been used in serial devices since the late 2000s. Conclusion. In general, the development of domestic chemical reconnaissance and control means goes in line with global trends. One of the modern trends is the development of combined devices based on a combination of several indication methods. Currently, the leading position is occupied by technical means of remote chemical reconnaissance and instruments, the operating principles of which are based on ion mobility spectrometry.